Masaža beba sa oštećenjem vida kao program rane intervencije usmerene na porodicu - Strižak, Nevena; Stanimirov, Ksenija; Anđelković, Marija (Specijalna edukacija i rehabilitacija, 2025)
The data indicate a constant increase in the number of children born and living with some form of visual impairment, which demands continuous professional work on designing special treatments, procedures, and practices that improve the quality of their lives and functioning. Families that have a child with developmental difficulties or a chronic illness face an extraordinary amount of anxiety, stress, and challenges throughout their lives. The realization that the child will need additional support, and that they may be forever different from other children of the same age, puts the family in front of a series of unexpected, difficult tasks. Visual impairment is such a situation. This paper will present theoretical considerations on infant massage as a support program that may be of particular importance in the population of visually impaired babies and discuss whether this programme could be recognized as a family-oriented early intervention. The review of available literature was conducted by searching electronic databases available through the KOBSON service, as well as Google Scholar and ResearchGate services. The literature review revealed that the development of the early intervention system in Serbia could focus on identifying local strengths and opportunities in creating services for children in our country. The issue of investing in new, non-institutional programs intended for families with babies and small children is being raised.
Keywords: infant massage; early intervention; family; visual impairment